2018
DOI: 10.1161/hypertensionaha.118.11718
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia Prevention Using Routine Versus Screening Test–Indicated Aspirin in Low-Risk Women

Abstract: The objective was to evaluate whether routine aspirin 75 mg is more cost-effective than the Fetal Medicine Foundation screen-and-treat approach for preeclampsia prevention in low-risk nulliparous women. A health economic decision analytical model was devised to estimate the discounted net health and cost outcomes of routine aspirin versus Fetal Medicine Foundation screening test–indicated aspirin for a cohort of 100 000 low-risk nulliparous women. Both strategies were compared with no intervention. A subanalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…Evaluation in the non-diabetic population has suggested that given the additional costs of screening, and the low cost and low side effect profile of prevention with low dose aspirin, it would be pragmatic to offer aspirin as intervention to all women without screening, which would provide improved outcomes at less cost. 87 Among women with pre-existing diabetes in the ASPRE trial, the rate of early onset preeclampsia, before 34 weeks, was 1.3% in the screen negative group. 86 For these women, where the risk of early onset preeclampsia in the screen negative group is relatively high, the argument for universal aspirin in preference to screening is even more convincing.…”
Section: Preeclampsia Screeningmentioning
confidence: 99%
“…Evaluation in the non-diabetic population has suggested that given the additional costs of screening, and the low cost and low side effect profile of prevention with low dose aspirin, it would be pragmatic to offer aspirin as intervention to all women without screening, which would provide improved outcomes at less cost. 87 Among women with pre-existing diabetes in the ASPRE trial, the rate of early onset preeclampsia, before 34 weeks, was 1.3% in the screen negative group. 86 For these women, where the risk of early onset preeclampsia in the screen negative group is relatively high, the argument for universal aspirin in preference to screening is even more convincing.…”
Section: Preeclampsia Screeningmentioning
confidence: 99%
“…Complementary laboratory assessments include the uterine artery pulsatility index by ultrasound and serum biomarkers. When both clinical and laboratory assessments are used, it is likely that all pregnant women at potential PE risk will be identified; however, such measurements come at a high cost 5, 27 …”
Section: Discussionmentioning
confidence: 99%
“…The unselected use of aspirin discouraged as a result. As such, an accurate predictive test that allows clinicians the ability of risk stratification for targeted aspirin dispensing 5 . The primary basis for a reliable predictive test is the combination of cost‐effectiveness from an acceptable false positive rate (FPR) and a high detection rate (DR) to receive both aspirin and differentiated obstetric care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Whether such algorithms are cost effective in comparison to other screening mechanisms or even a policy of low dose aspirin in every pregnancy has been put into question. [30] Presence of some risk factors, such as previous pregnancies affected by pre-eclampsia or intrauterine growth restriction are now considered sufficient to prompt the intervention with low dose aspirin. Evidence supporting other risk factors such as nulliparity, obesity and family history of pre-eclampsia is weaker, and intervention requires the combined presence of two or more factors.…”
Section: Introductionmentioning
confidence: 99%